Upaya Meningkatkan Hasil Belajar Sosiologi Melalui Metode Pembelajaran Inquiry pada Peserta Didik Kelas XI.IPS-2 SMAN 1 Lembah Melintang - Asmarni S.Pd (STKIP Pesisir Selatan, 2016)
AbstrakThe success of the learning objectives determined by many factors including the factor of teachers in implementing the learning process, one of which method is used to solve the above problems and to achieve the goal of education to the maximum, the teacher's role is very important and teachers are expected to have a good teaching method and is able to choose appropriate learning methods and in accordance with the concepts of subjects to be disampaikan.Permasalahan which is to be examined in this study is: Does the use of the inquiry learning methods to improve learning outcomes Sociology students of class XI IPS-2 SMAN 1 Valley Crossing? the purpose of this action research is to improve learning outcomes through the use of learning methods Sociology inquiri learner 2nd XI IPS SMAN 1 Loire Melintang.Penelitian using action research as much as two rounds. Each round consists of four phases: planning, implementation, observation and reflection. Goal of this research is the students Class XI IPS-2 SMAN 1 Valley Crossing. The data obtained are quantitative data and analysis results kualitatif.Dari the inquiry method of learning has a positive impact in improving the learning outcomes of students characterized by increased completeness of learners in each cycle, the first cycle (68.42%), the second cycle (86.84%) .Kesimpulan of this study learning method inquiri have a positive effect, which can increase learning outcomes of students shown by the average response of students stating that learners interested and are interested in learning methods inquiri so that they become motivated to learn.Keywords: Sociology, the inquiry method of learning, Learning Outcomes